An analysis of informed consent and clinical aspects regarding mental capacity in context of the Mental Health Care Act 17 of 2002 - Carstens, Pieter Albert, 1960- (University of Pretoria, 2015)
Dissertation (LLM)--University of Pretoria, 2015.